Learning by doing: collaborative conceptual modelling as a path forward in ecosystem-based management. (1st April 2021) - DePiper, Geret; Gaichas, Sarah; Muffley, Brandon; Ardini, Greg; Brust, Jeffrey; Coakley, Jessica; Dancy, Kiley; Elliott, G Warren; Leaning, Dustin C; Lipton, Douglas; McNamee, Jason; Perretti, Charles; et al.
Abstract: Managers, stakeholders, and scientists recognize the need for collaborative, transparent, integrated approaches to complex resource management issues, and frameworks to address these complex issues are developing. Through the course of 2019, the Mid-Atlantic Fishery Management Council developed a conceptual model of ecosystem linkages and risks for summer flounder, a species of recreational and commercial fisheries importance. The proximal aim of the model was to develop a list of integrated management questions that could be refined and addressed through a future quantitative management strategy evaluation. As such, this conceptual model served as a scoping tool. However, the true value of the conceptual model lays elsewhere: familiarizing resource managers historically focused on single-species management with the potential utility of an ecosystem approach to management. This paper details the goals and development of the conceptual model and situates this process in the broader context of best practices for collaborative open science and scientific reproducibility. Further, it highlights a successful path by which the shift towards ecosystem-based management can be actuated.